Developing Linguo-Cognitive Competence Among Learners Is A Multifaceted Process That Involves Enhancing Their Language Skills - Rakhimov Mansur Odiljonovich (Academia One Publishing, 2025)
In the contemporary landscape of globalized communication and knowledge economies, the goal of language education has transcended the traditional focus on grammatical accuracy and vocabulary acquisition. This article posits that the primary objective of modern language pedagogy should be the development of linguo-cognitive competence - a holistic construct that integrates linguistic skills with underlying cognitive processes. Linguocognitive competence is defined as the ability to not only use a language correctly but also to employ it strategically as a tool for complex thinking, problem-solving, critical analysis, and creative expression. This article explores the multifaceted nature of this developmental process, arguing that it involves the simultaneous and synergistic enhancement of declarative knowledge (knowing what) and procedural knowledge (knowing how). We will deconstruct the core components of this competence, including metacognitive awareness, conceptual thinking, and critical literacy. Furthermore, the article proposes a framework of pedagogical strategies, such as task-based learning, concept mapping, and scaffolded critical discourse analysis, which are designed to foster this higher-order integration. The conclusion underscores that by prioritizing linguo-cognitive competence, educators can empower learners to become not merely proficient speakers, but effective, adaptable, and discerning thinkers and communicators in any context
Keywords: globalized communication; knowledge economies; the goal of language education